Circulating Oxidized Low-Density Lipoproteins and Antibodies against Oxidized Low-Density Lipoproteins as Potential Biomarkers of Colorectal Cancer - Dorota Diakowska; Krzysztof Grabowski; Mirosław Nienartowicz; Paweł Zarębski; Kamila Fudalej; Krystyna Markocka-Mączka (Gastroenterology Research and Practice)
Introduction. The aim of the study was evaluation of the diagnostic utility of serum oxidized low-density lipoproteins (oxLDL), antibodies against oxLDLs (o-LAB), and CEA as risk markers of colorectal cancer (CRC). Material and Methods. The serum levels of study factors were measured in 73 patients with CRC and in 35 healthy controls who were gender- and BMI-matched to the study group. Concentrations of oxLDL, o-LAB, and CEA were detected in ELISA tests. Serum lipids, lipoproteins, and glucose levels were also coestimated. Results. Age and o-LAB were significant factors of CRC presence, but results of logistic regression analysis showed that both were weak predictors of CRC risk. Concentration of o-LAB was significantly higher in colon cancer than in rectal cancer, especially when the cancer was located in the right section of colon. Serum CEA levels were significantly elevated in the advanced stage of disease, primary tumor progression, angiolymphatic invasion, and presence of distant metastasis. Conclusions. Obtained results have demonstrated that oxLDL and o-LAB were not satisfactory risk markers of CRC. Although significant relation between o-LAB level and CRC is observed, it may be rather the result of individual differences in the host immune responses against cancer.